Indigenous Environmental Justice: Comparing the United States and Canada's Legal Frameworks for Endangered Species Conservation. Issue 4 (1st October 2016) - Olive, Andrea; Rabe, Andrew
ABSTRACT: Canada and the United States are both committed to the protection of endangered species. This article examines how the legal frameworks created around the US Endangered Species Act (ESA) and the Canadian Species at Risk Act (SARA) intersect with Indigenous environmental justice (EJ). Specifically, the distribution of benefits and burdens is examined since critical habitat designations can limit activity on Native American and First Nation tribal lands. Legal documents and recent court cases also give insight into Indigenous inclusion and recognition in conservation approaches in North America. Overall, it is argued that Canada's approach comes closer to EJ, but neither legal framework meets the criterion of genuine EJ for Native Americans and First Nations.